1992
DOI: 10.1111/j.1365-2222.1992.tb03098.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azelastine on the seasonal increase in non‐specific bronchial responsiveness to methacholine in pollen allergic patients. A randomized, double‐blind placebo‐controlled, crossover study

Abstract: Azelastine, a phthalazinone derivative, is a new potent, long acting, orally active anti-allergic compound with particularly strong H1-histamine receptor antagonistic effects which has been proven to possess in vitro and in vivo a number of anti-inflammatory properties. The aim of the present study was to investigate whether azelastine would be able to prevent and/or reverse the seasonal increase in non-specific bronchial responsiveness to methacholine in pollen allergic patients. Twelve atopic patients (5 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…At the same time, the use of bronchodilators was reduced by 40%. Azelastine (4 mg twice daily) reduced nasal but not bronchial symptoms and did not reduce the use of bronchodilators nor did it protect against an increase in bronchial methacholine sensitivity during the pollen season (21). Cetirizine (10 mg twice daily) protected better than terfenadine (60 mg twice daily) against grass pollen-induced asthma and nasal blockage in 43 grass pollen-allergic subjects, 12-74 years of age (22).…”
Section: Effects Of the New Generation Of Antihistaminesmentioning
confidence: 95%
“…At the same time, the use of bronchodilators was reduced by 40%. Azelastine (4 mg twice daily) reduced nasal but not bronchial symptoms and did not reduce the use of bronchodilators nor did it protect against an increase in bronchial methacholine sensitivity during the pollen season (21). Cetirizine (10 mg twice daily) protected better than terfenadine (60 mg twice daily) against grass pollen-induced asthma and nasal blockage in 43 grass pollen-allergic subjects, 12-74 years of age (22).…”
Section: Effects Of the New Generation Of Antihistaminesmentioning
confidence: 95%
“…While corticosteroids inhibit the late response [67] so do theophyllines [80], high doses of /3-agonists [81], long-acting /3-agonists [9], sodium cromoglycate [67], nedocromil sodium [82], H, antihistamines [83] and a leukotriene receptor antagonist [84], Where comparative studies have been made, the effect of corticosteroid and cromoglycate pretreatment are indistinguishable [67,85]. This is not the case in clinical asthma, however, in which clinical trials have shown corticosteroid therapy to be superior to both cromoglycate [86] and theophyllines [87], In contrast, cromoglycate has significantly greater protective effects than theophylline in this allergic challenge model [88] but the two are indistinguishable clinically [89], Furthermore, the airway protective effect of H]-antihistamines in the late asthmatic reaction to an allergen model is inconsistent with their clinical effect [58,90] and although a diet rich in eicosapentaenoic acid can modify leucocyte leukotriene production and alleviate the late airway response to allergen challenge [91] this dietary manipulation has not been found to have any beneficial effects in clinical asthma [91,92],…”
Section: Airway Allergen Challengementioning
confidence: 99%